Crop Farmers' Enterprise Information Needs in Reality Television Show Utilization in Oyo State, Nigeria - Olajide, Rasak; Opeyemi, Alabi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
The emerging scenario of robust Agricultural Extension and Advisory Services (AEAS) in Africa presupposes the need for Reality Television Shows (RTS) to support AEAS demand and delivery Systems. A variant of the entertainment-education (EE) genre, RTS provides an ample platform for effective AEAS. Given this, this study investigated crop farmers’ information needs in RTS utilization in Oyo State, Nigeria. A four-stage sampling procedure was used to select 140 crop farmers who own a television set randomly, while data was collected with the use of a structured questionnaire on respondents’ characteristics, perceived benefits and constraints to utilization of RTS and information needs on farmers’ crop enterprises from RTS. Data were analyzed using frequencies, percentages, means and PPMC at P= 0.05. Findings show that respondents were predominantly male (68.6%), married (65.7%) with tertiary education (40.0%), while mean age, farming experience and annual income were 46.10±13.395years 11.36±8.83years and N464464.29±95,805.94, respectively. The likelihood of RTS to facilitate the adoption of improved technologies (4.41±3.11) and the provision of information on key factors like marketing channels and production cost (2.73±3.11) were some of the perceived benefits by respondents. However, they had reservations about the language barrier (2.3643±4.9081) as a constraint to the maximal exploitation of the potentials of RTS. Respondents’ information need was high for irrigation system (2.61±2.54), harvesting activities (1.96±0.81), and marketing outlets (3.00±2.05), across production, harvesting and marketing information needs. It is recommended that proposed RTS should use local language for RTS dissemination, while addressing the most pressing information needs of the crop farmers.